Optimizing Avian Fertility: Caffeine Modulation of Sperm Motility in Red Junglefowl - Sarkar, Shishir; Kamruzzaman, Md.; Osti, Komal Laxmi; Salma, Ummay; Miah, Abdul Gaffar (International Journal of Applied Sciences and Biotechnology, 2025)
The Red Junglefowl (RJF; Gallus gallus) represents the wild ancestor of domesticated chickens yet its numbers experience reduction because of habitat destruction together with hunting practices and mixed gene flow. The improvement of reproductive biotechnology is an essential requirement for conservation initiatives. The study tested how caffeine impacts sperm motility together with kinematic parameters in RJF semen through CASA. Semen samples were collected from 20 mature RJF males then diluted using increasing caffeine levels (1, 2, 3 and 4 mg/ml) while maintaining a control group with 0 mg/ml of extender. The study determined sperm total motility, progressive motility, curvilinear velocity (VCL), straight-line velocity (VSL), average path velocity (VAP) at 0, 30 and 60 minutes. The sperm motility increased significantly when caffeine was added at 2 mg/ml concentration because total and progressive motility reached maximum levels (P